2013
DOI: 10.1155/2013/369180
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect ofElephantopus scaber L.on Liver Regeneration after Partial Hepatectomy

Abstract: Liver regeneration after partial hepatectomy (PHx) is a physiological response for maintaining homeostasis. The aim of this study is to investigate effects of Elephantopus scaber L.- (ESL-) induced liver regeneration on growth factors (HGF and IGF-1), cell cycle regulation, and apoptosis suppressed. In this study, we fed five Chinese medicinal herbs (1 g/kg/day), Codonopsis pilosula (CP, Dangshen), Salvia miltiorrhiza Bunge (SMB, Danshen,), Bupleurum kasi (BK, Chaihu), Elephantopus scaber L. (ESL, Teng-Khia-U)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Efficacy in the restoration of liver function and liver regeneration has been established. Our previous report highlights the potential of silymarin to enhance the growth factors such as the HGF at various time points [ 35 ]. Similarly, it should be noted, from the present study, that HGF as well as other growth factors such as TGF α and TGF β 1 is also stimulated by silymarin after PHx in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy in the restoration of liver function and liver regeneration has been established. Our previous report highlights the potential of silymarin to enhance the growth factors such as the HGF at various time points [ 35 ]. Similarly, it should be noted, from the present study, that HGF as well as other growth factors such as TGF α and TGF β 1 is also stimulated by silymarin after PHx in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, various natural products from plants are believed to have the effect of restoring or protecting the liver which is known as hepatoprotective (20). Research on plants as hepatoprotective is ongoing, including ES (21).…”
Section: Hepatoprotectivementioning
confidence: 99%
“…ES has traditionally been used as a liver tonic. Liver regeneration after partial hepatectomy is a physiological response to maintain homeostasis (21). In laboratory experiments, liver damage can be induced with alcohol or ethanol (6).…”
Section: Hepatoprotectivementioning
confidence: 99%
“…E. scaber contains flavonoids and saponins, and it potentially inhibits the aromatase enzyme, which converts testosterone into estradiol (oestrogen). Therefore, E. scaber can be used to suppress the production of oestrogen in pregnant women infected by Salmonella typhi, followed by normal secretion of prolactin [8,9]. We previously demonstrated that E. scaber combined with Polyscias obtusa significantly enhances the immune system, particularly in terms of CD4 + T cells, CD8 + T cells and TER119 + (a marker of erythrocytes) cells [3].…”
Section: Introductionmentioning
confidence: 99%